A qualitative analysis of technical and compositional constraints in FPV drone videography for vertical social media content video - Sarbeni, Irwan; Sugihartono, Ranang Agung; Suyanto, Suyanto; Supiarza, Hery; Pertiwi, Apsari Azimat (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2025)
The increasing dominance of vertical video formats on mobile-first platforms such as Instagram Reels and TikTok presents new challenges for First Person View (FPV) drone videography, especially when capturing natural landscapes. This study aims to investigate the technical and compositional constraints of FPV drones in producing vertical video content for social media. Using a qualitative case study approach, data were collected through field observation, interviews with 10 professional FPV pilots, and a supplementary online survey. The findings reveal key limitations, including fixed horizontal camera orientation, lack of gimbal-based stabilization, and control systems ergonomically optimized for horizontal framing. These constraints hinder smooth movement, reduce composition flexibility, and increase the difficulty of capturing high-quality vertical footage. Although some pilots attempt workarounds, such as custom camera mounts and post-production cropping, these solutions are often labor-intensive and compromise video quality. This study contributes practical insights for drone designers and content creators seeking to adapt FPV technology for vertical video production and offers a foundation for future research into hardware innovation and workflow adaptation in response to evolving social media trends.